Pax, Journey Home - Pennypacker, Sara, 1951-; Klassen, Jon (New York, NY : Balzer + Bray, an imprint of HarperCollinsPublishers, 2021)
It has been a year since newly orphaned Peter and his pet fox Pax, now a protective father, have seen each other, but their paths cross again when Paxs kit falls desperately ill forcing him to turn to the one human he knows he can trust.
Keywords: Fathers and daughters -- Juvenile fiction; Orphans -- Juvenile fiction; Families -- Juvenile fiction; Foxes -- Juvenile fiction; Foxes as pets -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Animal fiction